2020
DOI: 10.1111/codi.15334
|View full text |Cite
|
Sign up to set email alerts
|

National variations in perioperative assessment and surgical management of Crohn’s disease: a multicentre study

Abstract: Aim Crohn's disease (CD) requires a multidisciplinary approach and surgery should be undertaken by dedicated colorectal surgeons with audited outcomes. We present a national, multicentre study, with the aim to collect benchmark data on key performance indicators in CD surgery, to highlight areas where standards of CD surgery excel and to facilitate targeted quality improvement where indicated. Methods All patients undergoing ileocaecal or redo ileocolic resection in the participating centres for primary and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The present STROBE [11] compliant study evaluates the treatment of colonic CD in Italy. Details have been previously reported [12]. Briefly, after developing the study protocol, which was approved by the SICCR research board, the steering committee invited Italian colorectal units to join the initiative via an open call and newsletters.…”
Section: Study Settingsmentioning
confidence: 99%
“…The present STROBE [11] compliant study evaluates the treatment of colonic CD in Italy. Details have been previously reported [12]. Briefly, after developing the study protocol, which was approved by the SICCR research board, the steering committee invited Italian colorectal units to join the initiative via an open call and newsletters.…”
Section: Study Settingsmentioning
confidence: 99%
“…The Italian Society of Colorectal Surgery (SICCR) promoted the snapshot study "Current status of Crohn's disease surgery", which is a retrospective, multicentre, observational study [4] developed according to the STROBE checklist [5]. Ethical approval was obtained from the promoting centres and every participating centre had a named Principal Investigator, liaising with the local ethics committee.…”
Section: Study Settingsmentioning
confidence: 99%
“…Previous studies in CD surgery have demonstrated significant variability across different hospitals in the volume of surgical procedures performed per year, the short-term surgical outcomes, and the adoption of minimally invasive surgery [ 17 ]. It is not surprising to highlight variations in IBD surgical practice, as similarly, the wide range of available treatments for IBD has been shown to result in significant heterogeneity amongst physicians in the use of biologics and combination therapy, confirming the need for standardised pathways for the care of IBD patients [ 18 ], and guidelines of several international societies have been released to optimize CD outcomes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%